Development, validation and comparison of three detection methods for 9 volatile methylsiloxanes in food-contact silicone rubber products. (February 2019) - Feng, Di; Zhang, Xirong; Wang, Wenjuan; Li, Zhenzhen; Cao, Xueli
Abstract: The volatile methylisiloxanes (VMSs) D4, D5 and D6 have been included in the Candidate List of Substance of Very High Concern (SVHC) by European Chemicals Agency (ECHA) in June 2018. In response to the concerns from the recent SVHC, this study presents three pretreatment methods including purge and trap (P&T), solid-phase microextraction (SPME) and ultrasound-assisted solvent extraction (UASE) combined respectively with gas chromatography-mass spectrometry (GC-MS), for detection of 9 VMSs in food-contact silicone rubber products. Under their optimal operation conditions, three methods were validated. Compared with SPME-GC-MS and UASE-GC-MS, P&T-GC-MS method showed the lower method detection limits (8.40 × 10 −4 –1.95 × 10 −3  mg/kg), the higher recoveries (91.05%–97.48%) and the good %RSD (7.6–11.9%). Considering to be of sensitivity, accuracy, stability, fully-automatic and solvent-free operation, P&T-GC-MS method was finally applied to quantify 9 VMSs in 56 commercial food-contact silicone rubber products. The results showed that 8 VMSs were found and their total contents varied from 17.97 mg/kg to 645.27 mg/kg in the 28 silicone rubber teats, meanwhile, D3, D4, D5 and D6 were detected and their total contents varied from 5.80 mg/kg to 1.45 × 10 3  mg/kg in the 28 pieces of silicone rubber bakeware. Highlights: P&T, SPME and UASE combined respectively with GC-MS were developed for 9 VMSs in food-contact silicone rubber products. Three methods were validated and compared. P&T-GC-MS was superior to SPME-GC-MS and UASE-GC-MS. 9 VMSs in 56 commercial food-contact silicone rubber products were quantified by P&T-GC-MS. D4, D5 and D6 were high detection rate and high content.